An Empirical Study of the Determinants of Profit Forecast by Tunisian Managers - Boudiche, Myriam (Journal of Asian Business Strategy, 2013)
The aim of this paper is to empirically explain differences in levels of publication of forecast information observed in a sample of companies by a number of characteristics of these companies (such as the level of debt, age, size or level of profitability of companies observed). On the basis of a data relating to 50 Tunisian firms listed in the Tunisian Stock Exchange in 2010, our findings shows that profitable companies belonging to high-tech sectors and involve insiders in the decision provide more detailed and credible than other forward-looking statements.